2022
DOI: 10.1038/s41467-022-33395-6
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome dysbiosis in antibiotic-treated COVID-19 patients is associated with microbial translocation and bacteremia

Abstract: Although microbial populations in the gut microbiome are associated with COVID-19 severity, a causal impact on patient health has not been established. Here we provide evidence that gut microbiome dysbiosis is associated with translocation of bacteria into the blood during COVID-19, causing life-threatening secondary infections. We first demonstrate SARS-CoV-2 infection induces gut microbiome dysbiosis in mice, which correlated with alterations to Paneth cells and goblet cells, and markers of barrier permeabil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
68
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(103 citation statements)
references
References 100 publications
(139 reference statements)
8
68
0
Order By: Relevance
“…Interestingly, this study demonstrated that the shortest treatment (3 days) produced longer lasting microbiome effects in some bacterial taxa for several weeks. The convergence of COVID-19, antimicrobial treatment and the gut microbiome adds more complexity, which another group investigated [5]. They demonstrated structural changes and reduced antimicrobial factors in the intestinal mucosa of SARS-CoV-2-infected mice, and observed signs of barrier permeability.…”
Section: Antimicrobial Effects On the Gut Microbiomementioning
confidence: 99%
“…Interestingly, this study demonstrated that the shortest treatment (3 days) produced longer lasting microbiome effects in some bacterial taxa for several weeks. The convergence of COVID-19, antimicrobial treatment and the gut microbiome adds more complexity, which another group investigated [5]. They demonstrated structural changes and reduced antimicrobial factors in the intestinal mucosa of SARS-CoV-2-infected mice, and observed signs of barrier permeability.…”
Section: Antimicrobial Effects On the Gut Microbiomementioning
confidence: 99%
“…The gut microbiome, including the appendix that is now recognized as a non-vestigial well that maintains the microbiome [ 72 ], is recognized today for substantial influences on human health [ 30 , 31 , 32 , 73 , 74 , 75 , 76 ]. The microbiome impacts human health, both in the prevention of or acceleration of chronic diseases and in limiting or enhancing infectious diseases [ 16 , 30 , 31 , 32 , 73 , 74 , 75 , 76 ]. This includes the potential for acute infections in the intestine or in the appendix to radically alter organ-level health [ 73 , 74 , 75 , 76 ].…”
Section: Mechanisms Of Sars-cov-2 and Potential Opposing Effects Of F...mentioning
confidence: 99%
“…This includes the potential for acute infections in the intestine or in the appendix to radically alter organ-level health [ 73 , 74 , 75 , 76 ]. SARS-CoV-2 may be one of such infections, inducing gut microbiome dysbiosis that leads to enhanced proliferation of pathogenic microbial species, including anti-microbial resistant strains, and to the movement of harmful secondary pathogens into the bloodstream from the gut [ 30 , 73 ]. In a study of a murine model and, in parallel, of patients with COVID-19, substantial loss of microbiome diversity was observed with many of the human cases having a single taxa that accounted for >50% of the bacteria in their gut and the loss of diversity was associated with the presence of blood stream infections [ 30 ].…”
Section: Mechanisms Of Sars-cov-2 and Potential Opposing Effects Of F...mentioning
confidence: 99%
See 2 more Smart Citations